Description of noncovalent interactions involving π‐system with high precision: An assessment of RPA, MP2, and DFT‐D methods. Issue 17 (2nd April 2019) - Su, He; Wang, Hui; Wang, Hongyan; Lu, Yunxiang; Zhu, Zhengdan
Abstract : Efficient approaches with high precision are essential for understanding the formation and stability of noncovalent interaction complexes. Here, 21 noncovalent interaction complexes involving π‐system are selected and grouped in three subsets according to ETS–NOCV method: dispersion‐dominated, electrostatic‐dominated, and mixed. We mainly focus on examining the performance of random‐phase approximation (RPA) on these π systems. The tested RPA‐based method includes standard RPA and its variants including the related single excitations (SEs), renormalized single excitations (rSEs), second‐order screened exchange (SOSEX), and the renormalized second‐order perturbation theory (rPT2). The routine second‐order Møller–Plesset perturbation theory (MP2) and three popular DFT‐D functionals (M06‐2X‐D3, ωB97XD, and PBE‐D3(BJ)) are also assessed for comparison. In this work, besides the calculation of interaction energies at Dunning‐type aug‐cc‐pVDZ and aug‐cc‐pVTZ basis set, we also present a larger database of interaction energies calculated using MP2 and RPA methods with Dunning‐type aug‐cc‐pVQZ basis set. An accurate CCSD(T)/CBS scheme is used to provide benchmark database. In addition to the high‐level results, we also provide potential energy surfaces (PES) of different interaction type. Among all the tested methods, MP2 has a satisfactory performance on electrostatic‐dominated and mixed‐type systems, except for dispersion‐dominated systems. DFT‐D functionals, especially ωB97XD functional, has a balanced performance across all the tested systems. Importantly, for RPA‐based methods, the calculation accuracy can be dramatically improved by taking into account SE or exchange effects, especially in the mixed complexes. We conclude that rPT2 among all the test RPA‐based methods gives an overall satisfactory performance across different interaction types. © 2019 Wiley Periodicals, Inc. Abstract : For all the tested systems grouped in dispersion‐dominated, electrostatic‐dominated, and mixed, the performance of rPT2 and ωB97XD methods has been found as excellent for the precise description of noncovalent interactions involving π‐system. The inclusion of single excitation or exchange effects beyond the RPA is essential to improve the description of the noncovalent interaction.